Prospektywne mierniki nierównowagi finansów publicznych - generational accounting - Babczuk, Arkadiusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The subject of this article is a presentation of Generational Accounting - one of the most popular prospective measures of fiscal imbalance. The author characterizes method of calculation of this measure as well as its possible modifications. Then, Generational Accounting advantages and disadvantages are discussed. Finally, an assessment of selected countries' fiscal policy is presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 73-84